Metabolic dysregulation and emerging therapeutical targets for hepatocellular carcinoma - Danyu Du; Chan Liu; Mengyao Qin; Xiao Zhang; Tao Xi; Shengtao Yuan; Haiping Hao; Jing Xiong (Elsevier, 2022)
Hepatocellular carcinoma (HCC) is an aggressive human cancer with increasing incidence worldwide. Multiple efforts have been made to explore pharmaceutical therapies to treat HCC, such as targeted tyrosine kinase inhibitors, immune based therapies and combination of chemotherapy. However, limitations exist in current strategies including chemoresistance for instance. Tumor initiation and progression is driven by reprogramming of metabolism, in particular during HCC development. Recently, metabolic associated fatty liver disease (MAFLD), a reappraisal of new nomenclature for non-alcoholic fatty liver disease (NAFLD), indicates growing appreciation of metabolism in the pathogenesis of liver disease, including HCC, thereby suggesting new strategies by targeting abnormal metabolism for HCC treatment. In this review, we introduce directions by highlighting the metabolic targets in glucose, fatty acid, amino acid and glutamine metabolism, which are suitable for HCC pharmaceutical intervention. We also summarize and discuss current pharmaceutical agents and studies targeting deregulated metabolism during HCC treatment. Furthermore, opportunities and challenges in the discovery and development of HCC therapy targeting metabolism are discussed.